Changes in adolescent loneliness and concomitant changes in fear of negative evaluation and self-esteem. (January 2022) - Geukens, Flore; Maes, Marlies; Spithoven, Annette; Pouwels, J. Loes; Danneel, Sofie; Cillessen, Antonius H. N.; van den Berg, Yvonne H. M.; Goossens, Luc
Current theories of loneliness posit that biases in social information processing play a key role in the development and maintenance of loneliness. However, this assumption has rarely been tested in longitudinal research in adolescence. The current study concentrated on two constructs associated with such biases, that is, fear of negative evaluation and self-esteem. More specifically, we examined whether changes in loneliness were associated with simultaneous changes in fear of negative evaluation and self-esteem. A sample of Dutch adolescents ( N = 1, 174; 50% female) in Grades 7 to 10 completed well-established measures of loneliness, fear of negative evaluation, and self-esteem on four measurement occasions with yearly intervals. Correlations among both initial levels and rates of change for these three variables were examined using a Parallel Process Model (PPM). Adolescents scoring high on loneliness scored high on fear of negative evaluation, but low on self-esteem. Changes in loneliness were accompanied by changes in the same direction for fear of negative evaluation and in the opposite direction for self-esteem. These findings indicate that fear of negative evaluation and low self-esteem could indeed play a role in the development and maintenance of loneliness. Future research will need to clarify how exactly these variables can hamper re-affiliation efforts and lead to sustained loneliness over time.